Are parents an obstacle to gender-atypical occupational choices? - Wolter, Stefan C. [Verfasser]; Zöllner, Thea [Verfasser] (My University, 2024)
„Despite numerous measures intended to enhance gender equality, gender-specific study and career choices remain a persistent concern for policymakers and academics globally. We contribute to the literature on gendered career choices by focusing on explicitly stated parental preferences for their children’s occupations, using a large-scale randomized survey experiment with adults (N=5940) in Switzerland. The focus on parents (and hypothetical parents) is motivated by the observation that adolescents consistently mention their parents as the single most important factor influencing their career choices. The surveyed adults are presented with a realistic choice situation, in which their hypothetical daughter or son has been proposed two different training occupations. The pair of occupations presented to the adults is drawn from a random sample of 105 pairs of occupations, and the respondents are not informed about the gender distribution of the two occupations. Results show that adults are gender-neutral when advising a daughter but have a pronounced preference for male-dominated occupations when advising sons. Preferences are almost identical for parents and non-parents and across age cohorts of adults.“ (authors‘ abstract; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 2.4.5 Gender Mainstreaming; 300; Berufsorientierung; Berufswahl; Geschlechtsspezifische Faktoren; Männerberuf; Frauenberuf; Eltern; Einflussfaktor; Schweiz